Vitamin D and Vitamin D Binding Protein Levels in COVID-19 negative and positive intensive care unit patients: A prospective multicenter study - Örnek Diker, Vesile; Yılmaz, Gülseren; Düz, Muhammed Emin; Algemi, Mürvet; Köseoğlu, Mehmet; Öztürk Emre, Hümeyra; oğuz, OSMAN (Journal of Medical Biochemistry, 2024)
Background: Vitamin D binding protein plays a crucial role in regulating vitamin D levels by carrying vitamin D and its metabolites and immunological response by binding to endotoxins and fatty acids. We aimed to compare vitamin D, DBP, and specific inflammatory markers among intensive care unit (ICU) patients with and without the COVID-19 virus. Methods: This multicenter study conducted in two training and research hospitals included 37 (13 female) COVID-19-positive and 51 (34 female) COVID-19-negative ICU patients. 25(OH) vitamin D, DBP, c-reactive protein (CRP), procalcitonin (PCT), D-dimer, troponin T (TnT), interleukin 6 (IL-6) and ferritin levels, survival, mortality rates, duration of stay (ICU) were examined. Results: We observed higher ferritin and CRP levels, along with lower DBP, TnT and D-dimer levels, in patients with COVID-19. ICU patients with COVID-19 exhibited elevated mortality rates (Odds Ratio: 3.012, 95% Confidence Interval [1.252-7.248], p=0.013). However, there was no statistically significant correlation observed between mortality rates and Vitamin D or DBP levels across the entire ICU patient cohort. Conclusions: Vitamin d values ​​were found to be low in all intensive care patients, regardless of their covid 19 status. Contrary to the literature, COVID-19 patients had lower D-dimer and TNT levels than negative controls. However, COVID-19-positive ICU patients have decreased DBP. Further DBP gene polymorphisms studies are needed to explain this situation